A case of rabies outbreak in a bull-calf from Nigeria - Ahmad, I; Audu, SW; Kaltungo, BY; Dandare, SU; Muhammad, U; Sadiq, AY; Bawa, B; Abubakar, U (Journal of the Hellenic Veterinary Medical Society, 2023)
This paper describes a rabies outbreak in a bull-calf which led to euthanasia following manifestation of clinical signs of the disease. Infection was confirmed using a rapid immunochromatographic test of the homogenates from brain tissues (the brain stem, hippocampus and cerebellum) sample. Exposure to rabies virus (RABV) had resulted due to an attack by a free-roaming dog (FRD). Mass vaccination campaigns against rabies and improving biosecurity measures to limit access of free-roaming dogs to farms can prevent the occurrence of RABV in dogs, livestock animals and personnel at risk in Nigeria.